Joint transitivity for linear iterates - Sebastián Donoso; Andreas Koutsogiannis; Wenbo Sun (Forum of Mathematics, Sigma)
We establish sufficient and necessary conditions for the joint transitivity of linear iterates in a minimal topological dynamical system with commuting transformations. This result provides the first topological analogue of the classical Berend and Bergelson joint ergodicity criterion in measure-preserving systems.